Vocal distinctiveness of the Red Crossbill (Loxia curvirostra) on the island of Newfoundland, Canada. (2nd July 2014) - Hynes, Douglas P.; Miller, Edward H.
Abstract: Ten vocal types of Red Crossbill ( Loxia curvirostra ) are recognized in North America. Little is known about this species' vocalizations on the island of Newfoundland, where the subspecies L. c. percna (Bent 1912 ) was described on the basis of study skins collected in a single year from one area; subsequently a distinctive vocal type was proposed on the basis of one sound recording. We made field recordings (∼1000 min) of Red Crossbill vocalizations in Newfoundland to describe vocalizations and compare them with vocal types recognized elsewhere in North America. One class of call ("flight call"; class I call hereafter) was distinctive, and discriminant analysis distinguished 98% of Newfoundland class I calls from mainland North American and European samples. Class I calls of 5 (out of 83) Newfoundland birds resembled recognized vocal types from mainland North America. Other call classes ("excitement/alarm" and "chitter") of Newfoundland birds also differed from mainland North American samples. We conclude that several vocal types of Red Crossbill, one of which may represent L. c. percna, occur in Newfoundland. Samples from other areas are needed to determine whether the distinctive vocal type in insular Newfoundland (a) represents L. c. percna and (b) is restricted to Newfoundland or also occurs in other areas such as Cape Breton Island.